*This preview shows
page 1. Sign up
to
view the full content.*

**Unformatted text preview: **P ( x ). Since, in the formula for ( x ), one can choose any antiderivative of P ( x ), we take the above deFnite integral with a = 0. (Such a choice of a comes from the initial point x = 0 and makes it easy to satisfy the initial condition.) Therefore, the integrating factor ( x ) can be chosen as ( x ) = exp x Z p 1 + sin 2 t dt . Multiplying the dierential equaion by ( x ) and integrating from x = 0 to x = s , we obtain d [ ( x ) y ] dx = ( x ) x d [ ( x ) y ] = ( x ) x dx 48...

View
Full
Document